Potential land for agriculture development in three coastal districts of Ben Tre province in the Mekong delta, Vietnam - Chi Nguyen Phan; Tuan Huy Vuong; That Loc Ton; Thanh Vu Pham (Vietnam Journal of Science, Technology and Engineering, 2022)
The research objective was to determine the suitability of land regarding physical and economic conditions as a basis to support managers in planning effective agricultural development strategies that are suitable and sustainable for land potential in a future affected by climate change. In this research, physical and socio-economic data were collected by field surveys, household interviews (330 households), and agricultural manager discussions. Additionally, the methodology of land suitability evaluation was based on Food and Agriculture Organization (FAO) (1976 & 2007) and Geographic Information System (GIS) tools, which were used to determine suitability classifications for land-use types (under different physical and socio-economic conditions) in three coastal districts within the Ben Tre province. The results showed that agricultural production status in the research area was divided into three agro-ecological zones including the freshwater zone, brackish water zone, and saltwater zone of which the highest rate of agricultural land area was aquaculture. The next major proportion of agricultural area belonged to land for planting perennial crops and land for planting annual crops. Besides, 7 and 8 land suitability zones were determined, respectively, depending on physical and economic conditions, for 11 main landuse types. This research contributes toward basic knowledge that aims to support local decision makers in their transformation of agricultural land and adaptation of salinization in the future.